Juridical Review of the Phrase "Unlawful" in Decisions on Corruption Crimes in State-Owned Legal Entities - Purba, Marisi P.; Santoso, Aris Prio Agus; Aryono, Aryono (JIHAD : Jurnal Ilmu Hukum dan Administrasi, 2024)
In several court decisions in cases of criminal acts of corruption in State-Owned Enterprises (SOE), the phrase "against the law" is in Article 2 paragraph 1 of Law Number 31 of 1999 concerning the Eradication of Corruption Crimes as amended based on Law Number 20 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes (Anti Corruption Act) is interpreted broadly by referring to the explanation of these regulations. Because it relates to an offense, the phrase "against the law" should be interpreted by taking into account the principle of legality, the principle of nullum delictum nulla poena sine previa lege poenali. The use of a broad interpretation of the phrase "against the law" results in unclear differences between unlawful acts in the context of civil law and (onrechtmatige daad) and unlawful acts in the context of criminal law (wederrechtelijkheid). This results in the risk of criminalization of SOE officials, giving rise to fear in making business decisions. The formulation of the problem in this research is how to interpret the phrase "against the law" in article 2 paragraph (1) of the Corruption Law when it is related to cases of criminal acts of corruption in SOE and what is the judge's interpretation of the phrase "against the law" in decisions court for criminal acts of corruption in SOE. The research method used is a research method with a normative juridical approach. The results of the research show that the phrase "against the law" is interpreted broadly in the explanation of article 2 paragraph (1) of the Corruption Law, and judges in several corruption crime decisions interpreted the phrase "against the law" broadly, resulting in violations of the Standard Operating Procedure, Work Plan and The Company's Articles and other internal company regulations are interpreted as unlawful acts that can be considered a criminal act of corruption.